A perspective on characterization of porous materials: the melting line and triple point - An, Rong; Le, Renxi; Gubbins, Keith E.; Śliwinska-Bartkowiak, Malgorzata; Thommes, Matthias (Adsorption-Journal of the International Adsorption Society, 2025)
The most commonly used methods of characterization of mesoporous materials involve measurement of the adsorption isotherm for a simple gas at some low fixed temperature, usually the normal boiling point. Observation of the condensation pressure in the pores makes it possible to estimate the pore size distribution and the surface area. In this note we review experimental and molecular simulation results for the pressure-temperature phase diagram for adsorbates confined within nano-porous materials, and point out that both the triple point and the pressure-dependence of the melting line are strikingly different from these properties for the bulk adsorbate. We suggest that further investigation of these two properties, and of their underlying interpretation at the molecular-level, are worthy of further study, with a view to improved characterization of nano-porous materials.
CRIS-Team Scopus Importer:2025-04-01